Study of the Philosophy of Radicalism - Hasinah, Hasinah (Journal of Innovation in Teaching and Instructional Media, 2023)
An ideology known as radicalism is growing in society, advocating for change through violence. This is why many people opt for simple ways and make everything legal to meet all demands and desires. To better understand radicalism in philosophy, this article explores it in relation to religious, economic, political, and educational understandings. Article reviews are used in the writing process. Additionally, the findings indicate that religious radicalism stems from the mindset of its followers, who use violence to persuade those with different views to adopt their interpretation of the economic and spiritual stance, inspiring actions intended to weaken and change the status quo. Meanwhile, political radicalism refers to a mindset that seeks comprehensive and revolutionary transformation by forcefully overturning existing norms. Furthermore, educators can become radicalized teachers, school administrators can become radicalized teachers, and the community or parents of students can become radicalized teachers and schools through various forms of intimidation.